Study Protocol: Community Links to Establish Alcohol Recovery (CLEAR) for Women Leaving Jail - Johnson, Jennifer E. (Contemp Clin Trials, 2017)
PURPOSE: This article describes the protocol for a randomized effectiveness trial of a method to link alcohol use disordered women who are in pretrial jail detention with post-release 12-step mutual help groups. BACKGROUND: Jails serve 15 times more people per year than do prisons and have very short stays, posing few opportunities for treatment or treatment planning. Alcohol use is associated with poor post-jail psychosocial and health outcomes including sexually transmitted diseases and HIV, especially for women. At least weekly 12-step self-help group attendance in the months after release from jail has been associated with improvements in alcohol use and alcohol-related consequences. Linkage strategies improve 12-step attendance and alcohol outcomes among outpatients, but have not previously been tested in criminal justice populations. DESIGN: In the intervention condition, a 12-step volunteer meets once individually with an incarcerated woman while she is in jail and arranges to be in contact after release to accompany her to 12-step meetings. The control condition provides schedules for local 12-step meetings. Outcomes include percent days abstinent from alcohol (primary), 12-step meeting involvement, and fewer unprotected sexual occasions (secondary) after release from jail. We hypothesize that (1) 12-step involvement will mediate the intervention’s effect on alcohol use, and (2) percent days abstinent will mediate the intervention’s effect on STI/HIV risk-taking outcomes. Research methods accommodate logistical and philosophical hurdles including rapid turnover of commitments and unpredictable release times at the jail, possible post-randomization ineligibility due to sentencing, 12-step principles such as Nonaffiliation, and use of volunteers as interventionists.